2009
DOI: 10.1111/j.1360-0443.2009.02687.x
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis C virus infection among drug injectors in St Petersburg, Russia: social and molecular epidemiology of an endemic infection

Abstract: Aims-To understand the epidemiology and transmission patterns of hepatitis C virus (HCV), the predominant blood borne-pathogen infecting drug injectors (IDUs), in a part of the former Soviet Union.Design-Cross-sectional respondent driven sample of IDUs. Measurements-Participants were surveyed to collect demographic, medical, and both general and dyad specific drug injection and sexual behaviors. A blood sample was collected to detect antibodies to hepatitis C and to amplify viral RNA for molecular analysis. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
25
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 64 publications
2
25
0
1
Order By: Relevance
“…In this study 80% reported positive for HCV at baseline, which is corresponding with previous studies [1][2][3][4][5][6]. The NEP has a great role in diagnosing these as 70% of the HCV positive patients reported that they had been diagnosed at the NEP.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…In this study 80% reported positive for HCV at baseline, which is corresponding with previous studies [1][2][3][4][5][6]. The NEP has a great role in diagnosing these as 70% of the HCV positive patients reported that they had been diagnosed at the NEP.…”
Section: Discussionsupporting
confidence: 77%
“…The prevalence of hepatitis C virus (HCV) among injection drug users (IDUs) varies greatly around the world from 36% to 95% [1][2][3][4][5][6]. At the needle exchange program (NEP) in Malmö, 91% tested positive for HCV [1990][1991][1992][1993], and in the same study HCV infection kept spreading despite free access to clean injection tools.…”
Section: Introductionmentioning
confidence: 99%
“…With an estimated 83,000 individuals who inject drugs in St. Petersburg (Heimer and White, 2010), or about 1.8% of the population, HIV prevalence exceeds 50% (Eritsyan et al, 2013; Niccolai et al, 2010) and more than 90% are infected with HCV (Heimer et al, 2014; Paintsil et al, 2009). Mandatory HIV testing occurs in Russian prisons and it is where many individuals first learn of their HIV infection (Niccolai et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…In Russia the prevalence of HCV is estimated to be 80% or higher in some locations (Paintsil et al., 2009; Rhodes et al, 2005, 2006). While chronic HCV infection is an independent risk factor for cirrhosis and hepatocellular carcinoma, the synergistic effect of HCV infection and heavy alcohol consumption can hasten the progression to these disorders (Bellentani et al, 1999; Safdar and Schiff, 2004; Tagger et al, 1999).…”
Section: Introductionmentioning
confidence: 99%